RETRACTED: Pseudopyronine B: A Potent Antimicrobial and Anticancer Molecule Isolated from a Pseudomonas mosselii - Nishanth Kumar, S.; Aravind, S. R.; Jacob, Jubi; Gopinath, Geethu; Lankalapalli, Ravi S.; Sreelekha, T.T.; Dileep Kumar, B.S. (Frontiers in Microbiology, 2016)
In continuation of our search for new bioactive compounds from soil microbes, a fluorescent Pseudomonas strain isolated from paddy field soil of Kuttanad, Kerala, India was screened for the production of bioactive secondary metabolites. This strain was identified as Pseudomonas mosselii through 16S rDNA gene sequencing and the metabolites produced were purified through silica gel column chromatography and a single pure bioactive compound was isolated. The chemical structure of the compound was identified as Pseudopyronine B by NMR and HR-ESI-MS. Pseudopyronine B recorded significant antimicrobial activity especially against Gram positive bacteria and agriculturally important fungi. MTT assay was used for finding cell proliferation inhibition and Pseudopyronine B recorded significant antitumor activity against non small cell lung cancer cell (A549), and mouse melanoma cell (B16F10). MTT assay results showed that the growth of cancer cells was suppressed by Pseudopyronine B in both dose- and time-dependent manner. Acridine orange/ethidium bromide and hoechst stained cells indicated apoptosis induction by Pseudopyronine B and this was further confirmed by flow cytometry analysis using Annexin V. Cell cycle analysis also supports apoptosis by inducing G2/M accumulation in both A549 and B16F10 cells. Up-regulation of caspase 3 activity was also found in cells treated with Pseudopyronine B. Enhancement in the proliferation of lymphocytes suggested immunomodulatory activity of this compound. To the best of our knowledge, this is the first report on the isolation of Pseudopyronine B from Pseudomonas mosselii and its anticancer activity in A549 and B16F10 cells. This study has a significant contribution to the knowledge of Pseudopyronine B from Pseudomonas mosselii as potential sources of new drugs in the pharmacological industry, especially as potent antimicrobial and anticancer agent.